Pathogens of forrest trees in nurseries a minireview - Fendrihan, Sergiu (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The forest trees nurseries are attacked by different pathogens which are causing important damages and economic loss in forest commercial exploitations. One of the most important losses are in the tree nurseries, damaging the trees in their first stages of life Main pathogens for roots and stems are shown in this work. The fungi described may atack many agricultural cultures, and only some of them are specific for forest trees. The economic damages can be semnificatives. Some solutions for prevention and treatment of fungal pathogens attack are discussed further.